Fenomena Pemulung di Tempat Pembuangan Akhir (TPA) Bukit Pinang Kota Samarinda - Marpuah Marpuah; Eny Rochaida; Irwan Gani (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
Scavenger’s revenue still be below the edge of poverty and classified in cultural poverty. Characteristics of poverty scavenger based on the number of family members  that as many as 60% of scavengers have 5 family members, the highest educational scavenger only completed primary school, which was 60%. Based on aset ownership is only 60% who don’t have a motorcycle. The entire informants have power lines, and to meet the needs of clean water by 60% and 40% purchase using the facilities of the well. While based on the ownership of access to health care by 80% scavenger does not have a National Health Insurance card (JKN).Keywords: Phenomena of Scavenger